Benchmarking and application of the state-of-the-art uncertainty analysis methods XSUSA and SHARK-X. (March 2017) - Aures, A.; Bostelmann, F.; Hursin, M.; Leray, O.
Highlights: Application of the uncertainty analysis methods XSUSA and SHARK-X. Propagation of nuclear data uncertainty through PWR pin cell depletion calculation. Uncertainty quantification of eigenvalue, nuclide densities and Doppler coefficient. Top contributor to overall output uncertainty by sensitivity analysis. Comparison with SAMPLER and TSUNAMI of the SCALE code package. Abstract: This study presents collaborative work performed between GRS and PSI on benchmarking and application of the state-of-the-art uncertainty analysis methods XSUSA and SHARK-X. Applied to a PWR pin cell depletion calculation, both methods propagate input uncertainty from nuclear data to output uncertainty. The uncertainty of the multiplication factors, nuclide densities, and fuel temperature coefficients derived by both methods are compared at various burnup steps. Comparisons of these quantities are furthermore performed with the SAMPLER module of SCALE 6.2. The perturbation theory based TSUNAMI module of both SCALE 6.1 and SCALE 6.2 is additionally applied for comparisons of the reactivity coefficient.